Analysis of the Relationship Between Migraine and Cardiovascular Diseases: an Integrative Review - Lopes, Thiago Luís Marques; Coelho, Marina Karen Mendes; Sousa, Arthur Vitor Couto de; Ferreira, Eduarda Lima Verde; Filho, Hildel Freire Leite; Clarindo, José Fernando Muniz (Headache Medicine, 2023)
Full abstract in PDF